Kurikulum dan pembelajaran berbasis kesejahteraan semesta - Ari Kamayanti; Novrida Qudsi Lutfillah (Imanensi: Jurnal Ekonomi, Manajemen, dan Akuntansi Islam, 2020)
This paper aims to provide curriculum suggestions and forms of learning that are able to make every human being the result of learning become a manifestation of the Universal Welfare architecture. From criticizing the economic, management, and Islamic / Sharia accounting curricula, it can be seen that it is not enough just to "stick" the sharia label to the course. Subjects must contain the basic bases of universal welfare, such as courses on Critical Reading of the World, Islamic Epistemology, and Civilization. The learning strategies offered are: Critical and Spiritual Dialogue to Awaken the Meaning of Substances; b) Community Engagement; c) Concrete Projects of Cooperation with Various Interests; d) Use of Information Technology with Morals. Abstrak Tulisan ini bertujuan untuk memberikan usulan kurikulum dan bentuk pembelajaran yang mampu membuat setiap manusia hasil pembelajaran menjadi pewujud arsitektur Kesejahteraan Semesta. Dari menyampaikan kritik atas kurikulum ekonomi, manajemen, akuntansi Islam/Syariah, dapat diketahui bahwa tidaklah cukup sekadar “menempelkan” label syariah pada mata kuliah. Mata kuliah harus memuat basis dasar Kesejahteraan semesta, seperti mata kuliah Pembacaan Kritis Terhadap Dunia, Epistemologi Islam, dan Peradaban. Strategi pembelajaran yang ditawarkan yaitu: Dialog Kritis dan Spiritual untuk Menyadarkan Makna Substansi; b) Pelibatan dengan Masyarakat; c) Proyek Konkret Kerja Sama dengan Berbagai Kepentingan; d) Pemanfaatan Teknologi Informasi dengan Akhlak.